2023
DOI: 10.1590/1519-6984.242677
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastrointestinal parasitic infection in cows and buffaloes in Lower Dir, Khyber Pakhtunkhwa, Pakistan

Abstract: Gastrointestinal (GI) Parasitic infection is a hot issue for cattle management. There is variation of GI parasites effects in sex, age of cattle, drinking water condition, nutrition, and severity of infection. Studies on prevalence of GI parasites among cattle population in Dir Lower are lacking. A total of 40 farms were selected randomly in six tehsil namely Tehsil Adenzai, Tehsil Timergara, Tehsil Balambat, Tehsil Munda ,Tehsil Lalqala, Tehsil Khall. Freshly cattle fecal samples were collected randomly from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Furthermore, the high number of Haemonchus found in our samples should be considered an alarming signal, in consideration of the high pathogenic potential of the species belonging to this genus, although this is a quite common finding in a tropical area. In fact, it is in line with the results of the few studies conducted in cattle in Ethiopia [2][3][4]12] and in similar tropical countries, such as Zimbabwe [45], India [43,46] and Pakistan [42]. However, there were other reports in Ethiopia [34,35] that indicated a lower prevalence for Haemonchus, generally under 3%, but the estimation methods were not clearly described in most papers, as previously underlined.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, the high number of Haemonchus found in our samples should be considered an alarming signal, in consideration of the high pathogenic potential of the species belonging to this genus, although this is a quite common finding in a tropical area. In fact, it is in line with the results of the few studies conducted in cattle in Ethiopia [2][3][4]12] and in similar tropical countries, such as Zimbabwe [45], India [43,46] and Pakistan [42]. However, there were other reports in Ethiopia [34,35] that indicated a lower prevalence for Haemonchus, generally under 3%, but the estimation methods were not clearly described in most papers, as previously underlined.…”
Section: Discussionsupporting
confidence: 71%
“…), while other studies found a higher prevalence, as reported either for Moniezia spp. (24.8%) in Pakistan [42] or for Schistosoma spp., with values of 26%, 12% and 16.7%, in Kenya, Agew Awi Zone and South Wollo, respectively [33,40,43]. At the same time, in many areas of Ethiopia, Moniezia spp.…”
Section: Discussionmentioning
confidence: 96%
“…As cow has to face more stress than others animal categories during their pregnancy condition, lactation, and also in parturition and that is the high time to entry of parasites (Akter et al, 2015;Mustafa et al, 2022). Reduced resistance in cows or transient loss of acquired immunity close to parturition, as well as inadequate nutrition availability compared to their greater requirements are the key factors for their susceptibility to parasitic infestation (Arece et al, 2007;Khan et al, 2023). The genetics, physiological condition, grazing system, ration, and also management system of cows differ from bulls, heifers, and calves and that also act as risk factors for parasitism (Khatun et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Determining the relationship between age and infection risk is critical in identifying the part of the host population that contributes to parasite dynamics [5]. Lambs commonly have lower rates of gastrointestinal (GI) parasitic infections than adult sheeps [6]. However, lambs are more susceptible to helminths infection than adults, so the immune response of lambs is more important than adults.…”
Section: Introductionmentioning
confidence: 99%
“…Common endoparasites in buffalo including Entamoeba spp., Moniezia spp., Haemonchus spp. and Coccidians [6]. While in cattle, 3 genera of endoparasites were reported namely Haemonchus (Nematoda), Fasciola (Trematoda) and Paramphistomum (Trematoda) [9].…”
Section: Introductionmentioning
confidence: 99%